Da personagem máquina ao ciborgue em: "Zoom", "O Gravador" e "Quarto Selo (Fragmento)" de Rubem Fonseca - Daniel, Juliana (2009)
This dissertation propose to introduce the investigation of the character under the perspective of the relation alterity with the technology equipments in three short-stories by Ruben Fonseca: Zoom (1965); O Gravador (1965) and O quarto selo (Fragmento) (1967). The select short stories introduced an intimacy relation with the new communication technologies, in such a manner as the arrangement structure and the character gets, in this context, a new approach. It s in question the identity construction of the character and this part inside the short story, once that the other is the machine-subject. Beginning from the fundamental bakhtiniano concept the dialogue principle while alterity perception in the identity construction beyond Lévy conception about the relations between actual and virtual in technology universe, we considered the relation of the character with it s other the technological equipments in gradation that goes from virtual/simulation of the eyes and the voice throughout the camera zoom and the recorder, until the hybrid body of the real cyborg, like happens with the Exterminator in O quarto selo . However, at the same time, this other allows the character a possibility to expand itself, and it also can capture and destroy what is inherent in the human being. The technology doesn t cancel the contradictions, but, unlike, increase it them once more. We purpose, in this way, elaborate a reflection, although initial, about the function from the technological equipments to the characterization fonsequianas, aim at a reflection more wide open about the status creatures fiction in the contemporaneous period